PERLINDUNGAN HUKUM TERHADAP KORBAN PENIPUAN ONLINE DALAM TRANSAKSI E-COMMERCE MELALUI SOSIAL MEDIA FACEBOOK (STUDI KASUS: PENIPUAN YANG DIALAMI â€YISâ€) - Saputra, Muhammad Ikhwanu; Kuswanto, Irfan; Khalimy, Akhmad; Dzikirullah, Muhammad (MAGISTRA Law Review, 2025)
This research examines the prevalence of online fraud in e-commerce transactions conducted through the social media Facebook. Legal protections, as outlined in the Consumer Protection Law and the ITE Law, play an important role in addressing this challenge by providing avenues for victims to obtain redress and hold perpetrators accountable. Preventive measures, including public awareness campaigns and platform accountability, are critical to mitigating risks. This study underscores the need for collaborative efforts between government agencies, e-commerce platforms, and consumers to create a safer digital marketplace. The research contributes to the understanding of the dynamics of online fraud and offers insights to improve legal frameworks and enforcement strategies to protect consumers. Keywords: E-commerce, Online Fraud, Legal Protection